2022
DOI: 10.1038/s41586-022-05366-w
|View full text |Cite
|
Sign up to set email alerts
|

Bending forces and nucleotide state jointly regulate F-actin structure

Abstract: ATP-hydrolysis-coupled actin polymerization is a fundamental mechanism of cellular force generation1–3. In turn, force4,5 and actin filament (F-actin) nucleotide state6 regulate actin dynamics by tuning F-actin’s engagement of actin-binding proteins through mechanisms that are unclear. Here we show that the nucleotide state of actin modulates F-actin structural transitions evoked by bending forces. Cryo-electron microscopy structures of ADP–F-actin and ADP-Pi–F-actin with sufficient resolution to visualize bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 98 publications
(155 reference statements)
9
61
2
Order By: Relevance
“…The analysis of interprotomer interfaces in our four structures of actin isoforms ( Figure 4 , Figure 5 , Figure 4—figure supplement 1 ) showed that longitudinal interactions are mainly mediated by hydrophilic amino acids that are likely to enable interactions with water molecules that were recently shown to mediate interprotomer contacts within the filament core ( Figure 4 , Figure 4—figure supplement 1 ; Reynolds et al, 2022 ). Amino acid substitutions at the longitudinal interprotomer interface (also called long pitch helix interface) include L175/M176, T200/V201, Q224/N225, C271/A272, F278/Y279, and V286/I287.…”
Section: Resultsmentioning
confidence: 85%
“…The analysis of interprotomer interfaces in our four structures of actin isoforms ( Figure 4 , Figure 5 , Figure 4—figure supplement 1 ) showed that longitudinal interactions are mainly mediated by hydrophilic amino acids that are likely to enable interactions with water molecules that were recently shown to mediate interprotomer contacts within the filament core ( Figure 4 , Figure 4—figure supplement 1 ; Reynolds et al, 2022 ). Amino acid substitutions at the longitudinal interprotomer interface (also called long pitch helix interface) include L175/M176, T200/V201, Q224/N225, C271/A272, F278/Y279, and V286/I287.…”
Section: Resultsmentioning
confidence: 85%
“…Structural studies on the interaction of CH domains with F-actin have revealed that CH1 simultaneously interacts with two adjacent actin monomers and is sensitive to the torque/helicity of F-actin filaments (Hanein et al, 1998; Iwamoto et al, 2018; Kumari et al, 2020; Harris et al, 2020). Changes in the helical twist of F-actin filaments can be caused by mechanical tension, by interactions with actin-binding proteins (Harris et al, 2018; Jégou and Romet-Lemonne, 2020; Harris et al, 2020), or by the bending of F-actin filaments promoted by differences in the nucleotide states of actin monomers (Reynolds et al, 2022; Oosterheert et al, 2022). It is therefore possible that CH1 domains of different actin-binding proteins are predisposed to bind F-actin filaments with specific helical twists, which could explain their distinct but partly overlapping localisation patterns (Washington and Knecht, 2008; Harris et al, 2020; Jégou and Romet-Lemonne, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…While the structure of several ABPs could be inferred by studying them in isolation via X-ray crystallography (see examples [4,9]), high-resolution structures of F-actin bound to most of its interactors were, for a long time, unachievable due to helical assemblies remaining refractory to crystallization [19]. However, in recent years, breakthroughs in cryo-EM methodology have led to structures up to 2 Å resolution for F-actin alone [21][22][23][24][25], or at lower resolution when bound to full-length or truncated variants of their interactors [23,24,[26][27][28][29][30][31][32], or with filament-stabilizing toxins or peptides used for filament labeling [33][34][35][36]. Specifically, structural knowledge on interactions of toxins or peptides with F-actin has the potential for structure-guided developments of new labeling compounds to facilitate visualizing actin networks in migration and beyond.…”
Section: Cryo-em and Cryo-etpotential And Limitationsmentioning
confidence: 99%
“…Recently, two break-through studies by Oosterheert et al [ 21 ] and Reynolds et al [ 22 ] exemplified that F-actin represents a nearly ideal sample for cryo-EM structure determination, as they were able to derive structures of filaments in vitro in different nucleotide states at resolutions down to ∼2.2 Å. The nucleotide state did not result in large differences in F-actin conformation, in line with previous lower-resolution structures [ 84 , 85 ].…”
Section: Nucleation and Maintenance Of Branched Actin Networkmentioning
confidence: 99%